2018
DOI: 10.2196/jmir.9646
|View full text |Cite
|
Sign up to set email alerts
|

Drug Repositioning to Accelerate Drug Development Using Social Media Data: Computational Study on Parkinson Disease

Abstract: BackgroundDue to the high cost and low success rate in new drug development, systematic drug repositioning methods are exploited to find new indications for existing drugs.ObjectiveWe sought to propose a new computational drug repositioning method to identify repositioning drugs for Parkinson disease (PD).MethodsWe developed a novel heterogeneous network mining repositioning method that constructed a 3-layer network of disease, drug, and adverse drug reaction and involved user-generated data from online health… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 49 publications
0
11
0
Order By: Relevance
“…The use of AI is prevalent in drug discovery, and many pharmaceutical corporations have established in-house partnerships or initiatives with AI companies. Some organizations are currently using AI approaches to find novel uses for late-stage drug candidates or repurpose existing drugs [ 34 , 35 ]. However, data of sufficient quality are needed to train systems for COVID-19 AI implementation.…”
Section: Resultsmentioning
confidence: 99%
“…The use of AI is prevalent in drug discovery, and many pharmaceutical corporations have established in-house partnerships or initiatives with AI companies. Some organizations are currently using AI approaches to find novel uses for late-stage drug candidates or repurpose existing drugs [ 34 , 35 ]. However, data of sufficient quality are needed to train systems for COVID-19 AI implementation.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, of all the PD connections, 300 have a discovered drug therapy, and some of these drug therapies have previously been shown to be applicable for PD. For example Zhao et al 46 showed the drug repurposing potential between PD and Asthma, Alzheimer disease, Depression, Epilepsy, Multiple scleroris, Fatigue and Immunological disorders. Of these, Multiple sclerosis, immunological disorders and eplipesy were all part of the pairings discovered by our method too, giving further justifications for the domain-based pairings resulting in drug repurposing.…”
Section: Discussionmentioning
confidence: 99%
“…Another recently reported application of social media was a move for drug repositioning to accelerate drug development in Parkinson disease where, without social media, such development would likely be delayed. 19…”
Section: Education and Researchmentioning
confidence: 99%